Nurturing the phenotype: Environmental signals and transcriptional regulation of intestinal γδ T cells - Vogg*, Lisa; Winkler, Thomas H. (European Journal of Immunology, 2024)
The intestinal epithelium harbours a unique lymphocyte population, the intraepithelial lymphocytes (IELs). A large fraction of IELs is represented by γδ T cells. Their role in epithelial homeostasis and immune response is well documented, but a conclusive view of their developmental pathway is still missing. In this review, we discuss the existing literature as well as recent advances regarding the tissue adaptation of γδ IELs, both for the characteristic cytotoxic subset and the newly described noncytotoxic subset. We particularly highlight the environmental cues and the transcriptional regulation that equip γδ T cells with their IEL phenotype.
CRIS-Team Scopus Importer:2024-08-23
Keywords: IEL; Intestine; Tissue adaptation; Transcriptional regulation; γδ T cells